Pengaruh Stress Kerja, Keseimbangan Kehidupan Kerja, dan Kesejahteraan terhadap Keberlanjutan Kinerja (The Influence of Job Stress, Work-Life Balance, and Well-Being on Performance Sustainability) - Wiji Tri Wahyuni; Ignatius Soni kurniawan; Tri Ratna Purnamarini (STIE Malangkucecwara, 2026)
In Micro, Small, and Medium Enterprises (MSMEs) in the Special Region of Yogyakarta, several issues have been identified, including high job stress, low work life balance, and a lack of well being at workplace, all of which significantly hinder performance sustainability. This study aims to examine the influence of job stress, work life balance, and workplace well being on performance sustainability in MSMEs within the Special Region of Yogyakarta. The target population of this studi was MSME employees in the region, with samples collected using an accidental sampling technique. Data obtained from 54 respondents were analyzed using the Smart PLS 4 software. The findings reveal that job stress and work life balance have an insignificant effect on performance sustainability, while workplace well being has a significant positive effect. These results suggest that holistic support for employee well being is a key factor in maintaining long-term performance. The implications of this study provide valuable insights for MSME practitioners to emphasize human resource policies that enhance workplace well-being through the creation of supportive environments, open communication, and emotional balance among team members.